The impact of COVID-19 on young people's mental health, wellbeing and routine from a European perspective: A co-produced qualitative systematic review. - Lindsay H Dewa; Lily Roberts; Elizabeth Choong; Caroline Crandell; Ola Demkowicz; Emma Ashworth; Catia Branquinho; Steph Scott (PLoS ONE, 2024)
Background The impact of the Covid-19 pandemic on young people's (YP) mental health has been mixed. Systematic reviews to date have focused predominantly on quantitative studies and lacked involvement from YP with lived experience of mental health difficulties. Therefore, our primary aim was to conduct a qualitative systematic review to examine the perceived impact of the Covid-19 pandemic on YP's (aged 10-24) mental health and wellbeing across Europe. Methods and findings We searched MEDLINE, PsycINFO, Embase, Web of Science, MEDRXIV, OSF preprints, Google, and voluntary sector websites for studies published from 1st January 2020 to 15th November 2022. European studies were included if they reported qualitative data that could be extracted on YP's (aged 10-24) own perspectives of their experiences of Covid-19 and related disruptions to their mental health and wellbeing. Screening, data extraction and appraisal was conducted independently in duplicate by researchers and YP with lived experience of mental health difficulties (co-researchers). Confidence was assessed using the Confidence in the Evidence from Reviews of Qualitative Research (CERQual) approach. We co-produced an adapted narrative thematic synthesis with co-researchers. This study is registered with PROSPERO, CRD42021251578. We found 82 publications and included 77 unique studies in our narrative synthesis. Most studies were from the UK (n = 50; 65%); and generated data during the first Covid-19 wave (March-May 2020; n = 33; 43%). Across the 79,491 participants, views, and experiences of YP minoritised by ethnicity and sexual orientation, and from marginalised or vulnerable YP were limited. Five synthesised themes were identified: negative impact of pandemic information and restrictions on wellbeing; education and learning on wellbeing; social connection to prevent loneliness and disconnection; emotional, lifestyle and behavioural changes; and mental health support. YP's mental health and wellbeing across Europe were reported to have fluctuated during the pandemic. Challenges were similar but coping strategies to manage the impact of these challenges on mental health varied across person, study, and country. Short-term impacts were related to the consequences of changing restrictions on social connection, day-to-day lifestyle, and education set-up. However, YP identified potential issues in these areas going forward, and therefore stressed the importance of ongoing long-term support in education, learning and mental health post-Covid-19. Conclusions Our findings map onto the complex picture seen from quantitative systematic reviews regarding the impact of Covid-19 on YP's mental health. The comparatively little qualitative data found in our review means there is an urgent need for more high-quality qualitative research outside of the UK and/or about the experiences of minoritised groups to ensure all voices are heard and everyone is getting the support they need following the pandemic. YP's voices need to be prioritised in decision-making processes on education, self-care strategies, and mental health and wellbeing, to drive impactful, meaningful policy changes in anticipation of a future systemic crisis.